The effect of androgenic anabolic steroids on the susceptibility of the rat heart to ischaemia and reperfusion injury - Rossouw, Ellen (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2002.